Influence of genetic algorithm parameters on the docking efficiency with the SOL program - Katkova, E.V. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2012)
The key genetic algorithm parameters and their influence on the docking efficiency implemented in the SOL parallel program are analyzed. Tests were carried out with complexes of uPA (urokinase-type plasminogen activator) and co-crystallized ligands and were directed on the research of new inhibitors of uPA as potential antitumor drugs. The optimal parameters of the genetic algorithm are obtained for the single-run mode, i.e., for the docking of a single molecule, and for the virtual screening mode, i.e., for the docking of compound libraries. Tests were performed on the CHEBYSHEV and LOMONOSOV cluster supercomputers.